2024
DOI: 10.2138/am-2022-8632
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry and thermodynamic properties of zircon structure-type materials

Andrew C. Strzelecki,
Xiaodong Zhao,
Paul Estevenon
et al.

Abstract: Zircon-class ternary oxide compounds have an ideal chemical formula of ATO4, where A are commonly lanthanides and actinides, with T = As, P, Si, V. Their structure (I41/amd) accommodates a diverse chemistry on both A-and T-sites, giving rise to more than seventeen mineral end-members of five different mineral groups, and forty-five synthetic end-members.Because of their diverse chemical and physical properties, the zircon structure-types are of interest to a wide variety of fields and may be used as ceramic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 302 publications
0
3
0
Order By: Relevance
“…Furthermore, upon heating and crystallite growth hydroxyl groups began to leave Zr­(SiO 4 ) 1– x (OH) 4 x , because zircon can contain water (cf. e.g., refs ). This process may have not come to an end at 1250 °C, because the weight loss graphs were still slightly declining (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upon heating and crystallite growth hydroxyl groups began to leave Zr­(SiO 4 ) 1– x (OH) 4 x , because zircon can contain water (cf. e.g., refs ). This process may have not come to an end at 1250 °C, because the weight loss graphs were still slightly declining (cf.…”
Section: Discussionmentioning
confidence: 99%
“…1), have emerged as a promising candidate matrix for immobilizing minor actinides due to its remarkable attributes, such as minimal chemical reactivity, low solubility, and robust resistance to radiation-induced damage. 2,14–17 Additionally, aside from its role as a nuclear waste disposal matrix, zircon-structured phase is also being considered as an alteration form during the long-term nuclear waste storage. 18 Most actinide nuclei and the decay daughter nuclei have long half-lives, such as T 1/2, Pu-241 = 14.4 years and its second daughter nuclei T 1/2, Np-237 = 2.1 million years.…”
Section: Introductionmentioning
confidence: 99%
“…29 To date, there is also only one experimental study of CeSiO 4 under high pressure. 30 In practice, stetindite (CeSiO 4 ) can be served as a suitable analogue 17,31 to PuSiO 4 due to the inherent challenges associated with handling radioactive plutonium and synthetic challenges to acquire pure phase of PuSiO 4 , as cerium carries both +3 and +4 charges and exhibits similar ionic radii to plutonium, allows for more manageable experimentation. 32–35 In situ high-pressure Raman spectroscopy experiments and synchrotron X-ray diffraction have revealed that phase transition of stetindite differs from coffinite.…”
Section: Introductionmentioning
confidence: 99%